Performance of Composite and Monolithic Prefabricated Vertical Drains - Ali, Faisal; Kim Huat, Bujang (1992)
With the increasing use of prefabricated vertical drains in the improvement of soft clay there are many types of these drains, both composite (with geotextile wrapping) and monolithic (without geotextile wrapping), available in Malaysia. Some engineers have the impression that all drains perform satisfactorily. However, case studies have shown that there are cases where vertical drains failed to function. Therefore, there is a need to identify the drains which are not suitable or do not perform satisfactorily. This paper describes the various tests that have been carried out on two types of drain (i.e. one composite and one monolithic) to study their performance under lateral pressure. Test results show the importance of having a filter sleeve around the drain core. They also indicate that the type of geotextile wrapping affects the performance of the drain. A relatively stiff woven geotextile seems to be the most favour able